Control Interno De Las Recaudaciones De Impuestos Y Tasas; Y, Su Incidencia En La Información Financiera Para La Toma De Decisiones En El Gad Municipal Del Cantón Baba - Zamora Vera, Alexandra Josefina (2018)
In the Baba Canton, Province of Los Ríos, the investigation entitled "Internal Control of Tax and Rate Collections; and, its incidence in the financial information for the decision making in the Municipal GAD of the Baba Canton "whose main objective is to improve the policies of Internal Control for the correct handling of the collections of taxes and rates in the financial information for the taking of decisions. The specific objectives are aimed at improving the incidence of internal control, knowing the level of efficiency of financial information and determining what is involved in the mismanagement and affects the decision making of the Municipal GAD of Baba Canton The research methodology to be implemented was descriptive, it was developed in the administrative and financial area, applying an interview and surveys to a population of 41 people of the GAD Municipal del Cantón Baba.